Relationship between Supportive Services of Parents with Children Disabilities - Noor Al-Huda Satar S. K. Al-Kafajy; Nuhad Mohammad Al-Dorie (Medical Journal of Babylon)
Background: Disabilities refer to the existence of a fundamental difference from the average or the normal, and specifically. The estimates of disabled persons vary from one society to another, according to the conditions of society and its social, economic, and health conditions. Objectives: The study aimed to assess the social supportive services for children with special needs and to find out the relationship between services support for parents of children with disabilities. Materials and Methods: From December 2021 to March 2023, Babylon Health Directorate, Al Hillah city conducted a descriptive cross-sectional design study. Non-probability purposive sampling conducted in rehabilitation centers consists of 200 parents. Data were gathered using an interviewing approach, which took between 25 and 30 min to complete. A committee of 17 professionals verified the questionnaire. To assess the instrument’s dependability, a pilot study was carried out employing statistical and descriptive data analysis techniques, and the data were examined by SPSS version 20. Results: The results of the present study show the overall quality of life for parents with children special. The results of the present study showed poor responses related to supportive services of parents with children, and also the relationship results show that there is a significant relationship between supportive services with some demographical characteristics at P-value < 0.05. Conclusions: This study found the children with special needs received poor overall supportive services in the areas of physiotherapy, occupational therapy, social work, psychology, and technology. There was a correlation between supportive services for parents with children disabilities ratings and all underlying health factors for kids with exceptional needs.